Cross-Ethnic Voting: An Index of Centripetal Electoral Systems. Issue 3 (20th July 2021) - Reilly, Benjamin
Abstract: Centripetal approaches to democracy in divided societies seek to promote inter-ethnic accommodation and moderation by making politicians dependent on the electoral support of groups other than their own base. Such cross-ethnic voting stands in contrast to situations where politicians need only the support of their own co-ethnics to win elections. This distinction can be used to evaluate the utility of centripetal electoral systems in promoting voting across ethnic divides. To do so, this article begins by considering some critiques of centripetalism, showing that cross-ethnic voting is more common in both institutional design and actual practice than some critics believe. It then moves on to examine cases of cross-ethnic voting via ethnically designated party lists, cross-regional party formation rules, at-large communal or sectoral seat reservations, and uni-directional vote-pooling, using these cases to construct an index of strong, moderate and weak centripetal electoral systems.